SELF-TUNING CONTROL SYSTEM ALGORITHMS IMPROVEMENT FOR PROVIDING EFFICIENCY OF ITS STARTING REGIMES - Khobin, V. A.; Levinskyi, V. M.; Levinskyi, M. V. (Radio Electronics, Computer Science, Control, 2018)
Context. A whole series of technological type control objects have substantially nonlinear static characteristic, when gain through control channel changes in ten or more times. At the same time typical control systems with unchanged controller parameters lose their stability and switch to the position mode of operation. Automatic control systems (ACS) with self-tuning of the controller parameters allow to save a compromise between quality indicators and processes stability in the systems with such objects. Their algorithms should provide effective system functioning not only in steady-state, but also in transient modes, when set point changes, when control object is being transferred from the initial state, more often from idling, to the state of nominal load. The controlled variable in the start-up modes must not violate the procedural limits of the technological process, since it can lead to emergency situations. Objective. To improve the ACS algorithms with self-tuning for the start-up conditions of the control object, ensuring the completion of the self-tuning procedure during the start-up period and lowering the possibility of emergency situations. Method. Utilizing analysis of the advantageous and disadvantageous factors for the self-tuning procedure, using heuristic method, correction for the algorithms, which were developed earlier for steady-states, was proposed for the start-up period. Algorithms correction efficiency is verified by simulation of the system in the Simulink environment of the MatLab software package. Results. Computer experiments with models of alternative structures of the self-tuning system were planned and conducted. Obtained figures and numerical values characterize the efficiency of its operation in the start-up modes. Conclusions. To complete the self-tuning procedure during the start-up period and to prevent unacceptable dynamic control errors, it is necessary to: a) increase the controller gain and decrease the persistence of the filters in the self-tuning loop during the startup period; b) set the initial value of the control object model gain at the maximum possible level.